Karakteristik Campuran Aspal Porus Dengan Limbah Plastik Polietilena Tereftalat (PET) Sebagai Bahan Tambah Pada Aspal - Arif, Muhammad Isfan; Putra, Sasana; Herianto, Dwi; Sulistyorini, Rahayu (Universitas Lampung, 2023)
Plastic waste, which is one of the biggest environmental pollutants, can open up opportunities to be utilized in the field of highway construction because it is easy to obtain and has a more economical price as a porous asphalt mixture. Referring to this, a research was carried out on the characteristics of a mixture of porous asphalt with polyethylene terephthalate (PET) plastic waste as an additive to asphalt. The purpose of this study was to determine the effect of the use of PET plastic waste on the characteristics of porous asphalt mixtures. The method used is a laboratory scale experimental method based on 3 types of testing, namely marshall, cantabro loss and asphalt flow down. The gradation in this study used the open graded Australian Asphalt Pavement Association (AAPA) 2004. The test results showed that the addition of PET could improve the performance of porous asphalt mixtures. Stability, density, MQ, and VFA values increase with the addition of PET content so that they can prevent fractures due to traffic loads. The decrease in the cantabro loss value makes the mixture's resistance to disintegration better. addition of PET content up to 7.5% can reduce the flow value so that the mixture has optimal flexibility. However, the recommended PET content should be below 5% because in this study the penetration and ductility values did not meet the general specifications for 2018 Highways.